2020
DOI: 10.1109/access.2020.2987547
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Model for Financial Time Series Forecasting—Integration of EWT, ARIMA With The Improved ABC Optimized ELM

Abstract: The practical significances and complexities of financial time series analysis induce highly demand more reliable hybrid model that denoised the data efficiently, handled with both linear and nonlinear patterns in the data, to achieve more accurate results. This paper suggests a new forecasting hybrid model for financial time series data combined Empirical Wavelet Transform (EWT) technique with improved Artificial Bee Colony (ABC) algorithm, Extreme Learning Machine (ELM) neural network, and Auto-Regressive In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…In addition to neural network algorithms, there are other algorithms such as SVMs that are combined with wavelet transforms. e experimental results also showed that the hybrid model incorporating the wavelet transform is better than the prediction using a single algorithm [29][30][31][32]. DTW is a kind of elastic measurement for calculating time series similarity [33][34][35].…”
Section: Related Workmentioning
confidence: 97%
“…In addition to neural network algorithms, there are other algorithms such as SVMs that are combined with wavelet transforms. e experimental results also showed that the hybrid model incorporating the wavelet transform is better than the prediction using a single algorithm [29][30][31][32]. DTW is a kind of elastic measurement for calculating time series similarity [33][34][35].…”
Section: Related Workmentioning
confidence: 97%
“…For ABC-ELM algorithm [36], the parameters of model related to ABC algorithms are set as the population size n is 100, the number of employed foragers and onlookers are n/2, the limits of food sources Limit is set to 50, and the maximum iterative number is set to 50.…”
Section: Empirical Analysis On Credit Risk Of Small and Micromentioning
confidence: 99%
“…Only the authors of [ 13 ] implemented data mining methods on NBA game score prediction. The five well-known data mining methods, including multivariate adaptive regression splines (MARS), k-nearest neighbors (KNN), extreme learning machine (ELM), eXtreme gradient boosting (XGBoost), and stochastic gradient boosting (SGB), are used in this study for building an NBA game score prediction model, as they have been widely used in various applications such as public health [ 17 , 18 ], finance [ 19 , 20 ] and civil engineering [ 21 , 22 ]. Moreover, the five methods are also successfully applied in the sports outcomes prediction research [ 6 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%